Effects of Mexiletine on a Race-specific Mutation in Nav1.5 Associated With Long QT Syndrome - Wu, Xin; Li, Yawei; Hong, Liang (Frontiers in Physiology, 2022)
The voltage-gated sodium channel Nav1.5 plays an essential role in the generation and propagation of action potential in cardiomyocytes. Mutations in Nav1.5 have been associated with LQT syndrome, Brugada syndrome, and sudden arrhythmia death syndrome. Genetic studies showed that Nav1.5 mutations vary across race-ethnic groups. Here we investigated an Asian-specific mutation Nav1.5-P1090L associated with LQT syndrome. We found that Nav1.5-P1090L mutation perturbed the sodium channel function. It altered the gating process of the channel and exhibited an enhanced window current. Treatment with mexiletine reversed the depolarization shift of the steady-state inactivation produced by P1090L. Mexiletine also modified the recovery from steady-state inactivation and the development of inactivation of P1090L. It rescued the dysfunctional inactivation of P1090L and reduced the P1090L channel’s availability.